If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -9x = 9x + 19 Reorder the terms: -1 + -9x = 19 + 9x Solving -1 + -9x = 19 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -1 + -9x + -9x = 19 + 9x + -9x Combine like terms: -9x + -9x = -18x -1 + -18x = 19 + 9x + -9x Combine like terms: 9x + -9x = 0 -1 + -18x = 19 + 0 -1 + -18x = 19 Add '1' to each side of the equation. -1 + 1 + -18x = 19 + 1 Combine like terms: -1 + 1 = 0 0 + -18x = 19 + 1 -18x = 19 + 1 Combine like terms: 19 + 1 = 20 -18x = 20 Divide each side by '-18'. x = -1.111111111 Simplifying x = -1.111111111
| 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 | | 47+3=40 | | X=45 | | y=4-xsqaured | | 16y^2+28=0 | | 10x+11y= | | x^4+5x^2+49=0 | | -(-x-5)+5(x-9)=2(x+8)-2x+5 | | 3n+2=9 | | 2x=3(1-x)-(x-1) | | 2x^3-12x^2+24x-2=0 | | 3x-(x-2)=(2x-1)(-3x+9) | | (2x-1)(-3x+9)=0 | | 2(c-2)whenc=7 | | 3x-1=4(2x-5) | | 63-4x=5x+23 | | 0.4(3k-0.6)= | | 13-9x=73-23x | | 0.05x-.6=5.3 | | 5p-6+3p=12 | | 13h+6d-9d-7h=0 | | (4x-37).12=276 | | 3(d-8)-6=9(d+2) | | -17-4x=-7-7x | | x^2+2y^2=1 | | 0.5(8+2)=17 |